2019
DOI: 10.1016/j.rmcr.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A pyo-hydropneumothorax with sepsis, secondary to Gardnerella vaginalis infection in a post-partum female

Abstract: A 20 year old female, 14 days post partum, presented to the Emergency Department in severe respiratory distress. Imaging of her chest revealed a left tension hydropneumothorax with significant mediastinal displacement. A chest drain was inserted and over 4L of cloudy-brown malodourous fluid was drained. Gardnerella Vaginalis was isolated on culture of the fluid. The pyohydropneumothorax and associated sepsis, was refractory to management with a chest drain and antimicrobial therapy. She required a video-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Gardnerella spp. is also reported as the pathogen involved in some infrequent infections such as wound infection (Sturm, de Leeuw and de Pree 1983), tubo-ovarian abscess (Burgess, Daramola and Lacey 1997), meningitis (Berardi-Grassias et al 1988), retinal vasculitis (Neri et al 2009), cephalohematoma (Nightingale et al 1986), and hydropneumothorax (Murray et al 2019).…”
Section: Gardnerella Spp Beyond Bvmentioning
confidence: 99%
“…Gardnerella spp. is also reported as the pathogen involved in some infrequent infections such as wound infection (Sturm, de Leeuw and de Pree 1983), tubo-ovarian abscess (Burgess, Daramola and Lacey 1997), meningitis (Berardi-Grassias et al 1988), retinal vasculitis (Neri et al 2009), cephalohematoma (Nightingale et al 1986), and hydropneumothorax (Murray et al 2019).…”
Section: Gardnerella Spp Beyond Bvmentioning
confidence: 99%
“…2 Extravaginal infections by G. vaginalis such as bacteremia, joint infections, and spinal dural abscess, rarely occur, 5–7 while lung infections and pleural effusions in female patients have also been documented. 8 Similarly, studies have found that the vaginal Gardnerella biofilm is sexually transmitted, with some heterosexual couples found to share the same G. vaginalis strain, 9 indicating that it can also be found in the male genitalia. However, reports about infection of other parts of men are relatively rare.…”
Section: Discussionmentioning
confidence: 98%
“… Calvert et al 18 2005 Male 50 Multiple abscesses Smoked 20 cigarettes a day for 30 years and drank 25 units of alcohol a week. Right perinephric and pleural aspirates culture IV high dose benzylpenicillin, cefuroxime and metronidazole for 41 days→oral metronidazole 400 mg twice daily and amoxycillin 500 mg three times a day Bittar et al 25 2019 Male 20 Pulmonary infection Previously healthy Respiratory secretions for culture by mini bronchoalveolar lavage Intravenous Vancomycin and Piperacillin/Tazobactam for 11 days→ampicillin-sul bactam for 4 days→Vancomycin and Cefepime metronidazole treatment for 4 days→ceftriaxone and metronidazole MurrayL 8 2019 Female 20 Pyohydropneumothorax and associated respiratory sepsis 14 days post partum Isolation from pleural fluid Piperacillin-Tazobactam 4.5g TDS and Vancomycin 15mg/Kg (1g) BD→clindamycin 800mg IV TDS→ a video-assisted thoracoscopic surgery Tamlihat 29 2020 Male 45 VAP Cardiorespiratory arrest; post-anoxic encephalopathy; inhalation pneumonia. Protected distal bronchial sampling Amoxicillin-clavulanic acid; cefotaxime + metronidazole …”
Section: Discussionmentioning
confidence: 99%
“…Additional reports describe the septic form of gardnerellosis occurring in infants [ 18 ], and in female and male immunocompromised patients [ 24 , 25 ]. Moreover, urinary abnormalities and alcoholism have shown to be contributing factors to G. vaginalis bacteremia in males and occasional cases of sepsis have been described [ 9 , 24 , [26] , [27] , [28] , [29] , [30] ].…”
Section: Discussionmentioning
confidence: 99%